2014
DOI: 10.1186/1824-7288-40-53
|View full text |Cite
|
Sign up to set email alerts
|

Looking for new treatments of Infantile Colic

Abstract: Infantile colic is a common disturbance occurring in the first three months of life. It is a benign condition and one of the main causes of pediatric consultation in the early part of life because of its great impact on family life. Some pediatricians are prone to undervalue this issue mainly because of the lack of evidence based medicine guidelines. Up to now, there is no consensus concerning management and treatment. Literature reports growing evidence about the effectiveness of dietary, pharmacological, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 35 publications
0
75
0
8
Order By: Relevance
“…A study showed that most of the mothers knew of some type of alternative treatment such as bath with herbs, virgin tile and white rose, as well as sun exposure. They had perception about the effectiveness or not of the practices and some reported previous use or intention to do it after hospital discharge [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that most of the mothers knew of some type of alternative treatment such as bath with herbs, virgin tile and white rose, as well as sun exposure. They had perception about the effectiveness or not of the practices and some reported previous use or intention to do it after hospital discharge [27].…”
Section: Discussionmentioning
confidence: 99%
“…Завершающая фаза функционального созревания кишечника начинается при рождении ребенка [11]. Исследования последних лет подтвердили, что регуля-цию развития кишечника осуществляют амниотическая жидкость, молозиво, грудное молоко, микробиота, цир-кулирующие в крови факторы роста, глюкокортикостеро-иды и другие эндогенные факторы [12].…”
Section: этиопатогенез функциональных заболеваний у детей раннего возunclassified
“…Aynı şekilde standart mama ile yeterli ağırlık artımı var ve inek sütü proteini alerjisi öykü ve semptomu yoksa hidrolize mamaya geçiş önerilmemektedir (40). Kolikli bebeklerde laktaz enzimli ya da liften zengin mamaların ve laktaz enziminin kullanımı ile ilgili yeterli veri olmadığı da çalışmalarda gösterilmiştir (38). Alternatif besinler içinde oral sükroz kullanımı bir dönem önerilmiş olup çalışma-larda bu konuda yeterli verinin olmaması nedeniyle artık rutinde önerilme-mektedir (46).…”
Section: Beslenme öNerileri Ve Diyet Değişikliğiunclassified